2018
DOI: 10.1155/2018/2713291
|View full text |Cite
|
Sign up to set email alerts
|

Study on Microstructure Effect of Carbon Black Particles in Filled Rubber Composites

Abstract: The cross sections of blended natural/styrene-butadiene (NSBR) composites filled with different volume fractions of carbon particles were observed using a Quanta 250 scanning electron microscope. In addition, the sizes and distributions of the carbon particles were analyzed using Nano Measurer. A two-dimensional representative volume element model (RVE) for a rubber composite reinforced with circular carbon particles was established, and the uniaxial tensile behaviors of polymer nanocomposites with different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The GRT particles are 250 μm length, and the surface area per unit volume is less than that of the HAF carbon black particles (maximum 250 nm) or its cluster (maximum 460 nm). 49…”
Section: Discussionmentioning
confidence: 99%
“…The GRT particles are 250 μm length, and the surface area per unit volume is less than that of the HAF carbon black particles (maximum 250 nm) or its cluster (maximum 460 nm). 49…”
Section: Discussionmentioning
confidence: 99%
“…1a and b. Previous studies have reported that these small grains are CB aggregates [42][43][44] , however, this information was insufficient to conclude that the grain structures exclusively contained CB fillers. Therefore, EDS analysis was performed on a particular grain to conduct a comprehensive analysis of the elemental composition, as observed in Figs.…”
Section: Cb Detection Using Sem and Afmmentioning
confidence: 90%
“…Similarly, the preparation of flat specimens with thicknesses between 20 nm and 100 nm is necessary for CB detection using TEM, which have more stringent requirements 21,22 . Furthermore, SEM cannot clearly distinguish between CB and rubber matrix because most organic elastomers and CB are mainly composed of carbon atoms 23 . Therefore, research on rubber compounds necessitates the development of instrumentation that can detect and identify CB aggregates without the need for pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon composites have become a crucial component in modern technology, with numerous applications in military, civilian, energy, medical, and environmental fields. Polymer composites, made with affordable materials and equipment, are easy to produce and offer both process ability and cost-effectiveness [5][6][7].Composite materials are produced by combining or merging different materials or qualities in which the component elements are individually distinct, or, two or more phases combined physically, which result in a new material that has excellent features if compared to the features of the individual phases [8][9][10].In opposing to alloys, every phase of composites keeps its distinguished physical, mechanical, and chemical properties [9,11,12].The essential utilities of composites are good stiffness, high specific strength, and good electrical and thermal properties results. In addition to lightweights when they are compared with alloys or ceramics products [13,14].…”
Section: Introductionmentioning
confidence: 99%